1998
DOI: 10.1093/oxfordjournals.bjc.a014258
|View full text |Cite
|
Sign up to set email alerts
|

FEAR OF CRIME AND CRIMINAL VICTIMIZATION: Testing a Theory of Psychological Incapacitation of the 'Stressor' Based on Downward Comparison Processes

Abstract: The empirical evidence supporting a fear-criminal victimization relationship is relatively weak and mixed. A fear-victimization model is developed which Fear and Victimization: Theoretical AspectsIn psychological analyses of emotions the cognitive paradigm is broadly adhered to (Frijda 1988). It assumes that emotions are produced by the person's interpretation of a psychologically significant situation (Berkowitz 1993). Cognitive theory highlights the importance of thoughts, interpretations, appraisals or judg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 14 publications
1
37
0
7
Order By: Relevance
“….erraro 1995), (b) vulnerability (e.g. Killias 1990;Killias and Clerici 2000;Warr 1984) and (c) experience of crime (Hale 1996:103ff;Winkel 1998). …”
Section: Discussionmentioning
confidence: 99%
“….erraro 1995), (b) vulnerability (e.g. Killias 1990;Killias and Clerici 2000;Warr 1984) and (c) experience of crime (Hale 1996:103ff;Winkel 1998). …”
Section: Discussionmentioning
confidence: 99%
“…The findings match previous research. Those who perceived themselves as most likely to be victims also showed a higher fear of victimization (Box et al, 1988;Cook & Fox, 2011;Gainey et al, 2011;Lee & HilinskiRosick, 2012;Ozascilar, 2013;Warr & Stafford, 1983;Winkel, 1998). This provides further evidence for the transferability of findings from the traditional to the cyber domain.…”
Section: Discussionmentioning
confidence: 76%
“…One explanation might be that fear includes a sense of vulnerability, both in terms of perceived likelihood of risk and perceived seriousness of the risk (Hale, 1996). Winkel (1998) also referred to perceived likelihood of risk as 'subjective victimization risk' and 'perceived negative impact', with the latter influencing fear more so than subjective victimization risk. This indirectly supports the link between fear and vulnerability to risk.…”
Section: Introductionmentioning
confidence: 99%
“…Chockalingam and Srinivasan's (2009) research suggested victimization had no impact on fear of crime among college students in India and was inversely associated with fear among college students in Japan. Winkel's (1998) analyses of longitudinal data from the Netherlands showed that crime victims expressed enhanced concern about crime immediately after the victimization incident but, as they recovered from the incident, they gained confidence in their abilities to cope with crime and became less concerned about victimization than persons who had not been victimized. Weinrath and Gartrell's (1996) analysis of data from Edmonton, Alberta (Canada) indicated that assault victimization was associated with heightened fear of crime among young adults, but reduced fear of crime among the elderly.…”
Section: Literature Reviewmentioning
confidence: 99%